Genome sequences reveal global dispersal routes and suggest convergent genetic adaptations in seahorse evolution - Chunyan Li (Nature Portfolio, 2021)
A new seahorse genome and the re-sequenced genomes of 21 other species shed new light on the evolutionary origin and global dispersal routes of seahorses, and show that bony spines—a key adaptation against predation—probably evolved multiple times via independent substitutions in the bmp3 gene.